(untitled) (UNIZIK Journal of Agricultural Economics and Extension, 2024)
Arc welding produces oxide dusts and fumes of Cadmium (Cd), and other heavy metals in the cause of their unregulated activities; and are exposed to these fumes either through inhalation, skin contact or ingestion. This study aims to determine the blood Cd levels and their effects on liver Biomarkers among Arc welders in Enugu. Blood samples were collected from arc welders who were all males (n = 50), with age ranging from 18 - 65 years, also from control group (n = 50) with age range of 18-65 years. 5ml of blood was dispensed into plain tubes for biochemical markers assay respectively. Serum for Biochemical assays was stored frozen at -20oC pending analysis. Analysis was performed using standard methods. Data was analyzed using statistical package for social sciences version 22 and student t-test to compare means between control and study groups. Statistically high levels of serum cadmium and liver makers were seen among exposed participants when compared to the non exposed (control group); Cd [0.0111 ± 0.0046, 0.0074 ± 0.0058; p< 0.05], ALT [18.27 ± 8.8, 16.80 ± 5.9; P< 0.05], AST [23.41 ± 7.6, 19.50 ± 3.4; p< 0.05], ALP [86.92 ± 29.2, 76.90 ± 18.11; p< 0.05]. No relationship between serum cadmium and liver biomakers were observed Cd and ALT (r = 0.112; p=0.450), Cd and AST (r = 0.086; p=0.561), Cd and ALP (r = 0.185; p=0.208). We therefore conclude that exposure to heavy metals like cadmium indicate higher absorption of these metals among welders which directly can impair liver function, Regular monitoring of these heavy metals’ levels, liver function tests among occupationally exposed individuals is strongly advocated.